Ambiguity, manageability and the orchestration of organisational change: a case study of an English Premier League Academy Manager - Gibson, L.; Groom, R. (Sports Coaching Review, 2018)
An academy is an organisational context operated by professional football clubs, governed by the rules of the English Football Association and the English Premier League. Academies provide coaching and education for youth football players aged from under 9 to under 21. The Academy Manager is responsible for the strategic leadership and operation of the club`s academy. This includes implementing the club`s philosophy, coaching and games programme, player education, and the management of academy staff. The purpose of this paper is to explore the experiences of Simon [pseudonym], an English Premier League Academy Manager, when implementing organisational change within an academy. Data were collected from a work-based diary and four in-depth semi-structured interviews. The notion of orchestration is used as an analytical frame to make sense of Simon`s experiences through the change process and further our understanding of the social complexities of organisational change in elite sporting environments.